2021
DOI: 10.1108/k-05-2021-0420
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing and human resource management: systematic literature review and future research agenda

Abstract: PurposeThis study aims to provide an overview of what characterizes the current state of research in the field of cloud computing use in human resource management (HRM) with the identification, analysis and classification of the existing literature and lines of research addressed and to provide guidance for future research.Design/methodology/approachThe systematic literature review (SLR) technique has been used to identify, select, analyze and evaluate the existing publications on cloud computing and HRM. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The objective of the research is to study the intersection between AI, art, and the CE. An analysis of search strings in previous studies e.g., Novais et al [ 71 ]; Maqueira et al [ 72 ] and a brainstorming session among the authors helped identify search keywords related to the research objective. A search string was created using simple operators, including truncated characters (e.g., *, “exact phrase”) and Boolean operators (e.g., AND, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the research is to study the intersection between AI, art, and the CE. An analysis of search strings in previous studies e.g., Novais et al [ 71 ]; Maqueira et al [ 72 ] and a brainstorming session among the authors helped identify search keywords related to the research objective. A search string was created using simple operators, including truncated characters (e.g., *, “exact phrase”) and Boolean operators (e.g., AND, OR).…”
Section: Methodsmentioning
confidence: 99%
“…The objective pursued in the evaluation phase is to discard those studies that are not relevant to the object of the investigation. To do so, the exclusion criteria were defined [ 32 , 72 , 73 ]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Two decisions are essential at this stage: choice of search engine and formulation of search strings. Web of Science (WoS) was selected as the search engine as it offers exhaustive coverage of the field with high‐quality international academic publications from influential publishers (Garcia‐Buendia et al, 2021; Marín et al, 2021; Olawumi & Chan, 2018; Wamba & Queiroz, 2020). Authors agreed on a selection of search keywords based on the previous literature (Pagliosa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Several methods that included thematic analysis/synthesis with metacognitive mind maps, qualitative comparative, meta‐summary and content analysis were considered for the research synthesis (Barnett‐Page & Thomas, 2009; Garza‐Reyes, 2015; Thomas & Harden, 2008). Descriptive analysis was adopted for this research as it does not infer the human being and enables a variety of research data and statistics to be elaborated and demonstrated, thus providing a more quantitative view of the entire study (Marín et al, 2021). Content analysis, in which human inference occurs, was also used to provide a metacognitive analysis of the researched articles and a thematic synthesis that allows a comprehensive analysis of all the articles used in the research, such as benefits, barriers, category and research approach.…”
Section: Methodsmentioning
confidence: 99%